2020
DOI: 10.1101/2020.04.02.022541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Nimbolide-Based Kinase Degrader Preferentially Degrades Oncogenic BCR-ABL

Abstract: Targeted protein degradation (TPD) and proteolysis-targeting chimeras (PROTACs) have arisen as powerful therapeutic modalities for degrading specific protein targets in a proteasome-dependent manner.However, a major limitation to broader TPD applications is the lack of E3 ligase recruiters. Recently, we discovered the natural product nimbolide as a covalent ligand for the E3 ligase RNF114. When linked to the BET family inhibitor JQ1, the resulting heterobifunctional PROTAC molecule was capable of selectively d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…To further demonstrate the utility of our fully synthetic RNF114 recruiter EN219 in degrading other more challenging protein targets, we synthesized a degrader linking EN219 to the BCR-ABL inhibitor dasatinib, ML 2-23 and ML 2-22, bearing a longer PEG3 linker and a shorter C3 alkyl linker, respectively (Figures 4A and S4F). For this particular target, ML 2-23 with the longer linker showed more robust degradation of BCR-ABL in K562 leukemia cells compared with ML 2-22, consistent with previously observed structure-activity relationships of nimbolide-based BCR-ABL degraders (Figures 4B, 4C, and S4G) (Tong et al, 2020). Consistent with ML 2-23 engaging BCR-ABL in cells, we observed inhibition of CRKL phosphorylation, a downstream substrate of BCR-ABL signaling (Figures 4B and 4C).…”
Section: En219-based Rnf114 Recruiter In Tpd Applicationssupporting
confidence: 89%
See 3 more Smart Citations
“…To further demonstrate the utility of our fully synthetic RNF114 recruiter EN219 in degrading other more challenging protein targets, we synthesized a degrader linking EN219 to the BCR-ABL inhibitor dasatinib, ML 2-23 and ML 2-22, bearing a longer PEG3 linker and a shorter C3 alkyl linker, respectively (Figures 4A and S4F). For this particular target, ML 2-23 with the longer linker showed more robust degradation of BCR-ABL in K562 leukemia cells compared with ML 2-22, consistent with previously observed structure-activity relationships of nimbolide-based BCR-ABL degraders (Figures 4B, 4C, and S4G) (Tong et al, 2020). Consistent with ML 2-23 engaging BCR-ABL in cells, we observed inhibition of CRKL phosphorylation, a downstream substrate of BCR-ABL signaling (Figures 4B and 4C).…”
Section: En219-based Rnf114 Recruiter In Tpd Applicationssupporting
confidence: 89%
“…Interestingly, EN219 showed preferential degradation of BCR-ABL compared with c-ABL, compared with several previous BCR-ABL degraders utilizing cereblon or VHL recruiters that showed opposite selectivity (Figures 4B and 4C) (Burslem et al, 2019;Lai et al, 2016). This preferential degradation was also observed with the equivalent nimbolide-based degrader (Tong et al, 2020). We further showed that this loss of BCR-ABL and c-ABL was not due to transcriptional downregulation of these genes, since BCR-ABL mRNA levels remained unchanged and we observed a likely compensatory increase in c-ABL mRNA levels (Figure S4H).…”
Section: En219-based Rnf114 Recruiter In Tpd Applicationsmentioning
confidence: 61%
See 2 more Smart Citations
“…The successful ubiquitination of neo-substrates often reflects their ability to form de novo protein-protein interfaces with the recruited E3 ligase (Gadd et al, 2017;Nowak et al, 2018). For example, recent studies show that degradation by bifunctional multi-kinase degraders often depends on stable ternary complex formation, and that degradation selectivity may vary according to the recruited E3 ligase (Tong et al, 2020;Bondeson et al, 2018;Lai et al, 2015). We were therefore interested in extending COFFEE to additional neo-substrates by labeling VHL with dasatinib, a promiscuous kinase inhibitor that engages at least 10 kinases with an apparent Ki < 100 nM, in addition to its primary target, BCR-ABL (Klaeger et al, 2017;Montenegro et al, 2020;Leonard et al, 2016).…”
Section: Ll Brief Communication Electroporation Of Dasatinib-functionalized Vhl Induces Kinase Degradationmentioning
confidence: 99%